Rapid adoption of electronic health record and health information exchange among assisted living communities, 2010–2018. (21st February 2022) - Lin, Sunny C; Tunalilar, Ozcan
Abstract: Adoption of electronic health records (EHRs) and health information exchange (HIE) is a key tool to improving the quality of care in assisted living communities (ALC). We examined whether EHRs were being used in ALC to support HIE in 2010 and 2018. We found that adoption of EHR and HIE functions increased substantially over the study period. However, adoption of HIE functions lagged significantly behind EHR functions in both 2010 and 2018 and was accompanied by growing disparities in the adoption of EHR functions among smaller, nonchain, and for-profit communities. To improve the quality of care for this important and growing population, targeted policies are needed to support the adoption of both EHR and HIE functions in ALC.